Product Differentiation and Packaging of Fish Floss at the Rianilis Business Group in Tawiri District, Ambon City - Sahusilawane, Wildoms; Hiariey, Lilian Sarah; Nanlohy, Hellen; Ruban, Angela (Pascasarjana Universitas Mataram, 2024)
The abundant potential of Ambon City's fishery resources allows many producers to use them as a source of income. Rianilis is one of the business groups in Tawiri Village that takes advantage of this potential by producing shredded tuna. The problems faced in running the business are limited market share so that production cannot be carried out optimally and packaging that is not hygienic to maintain product quality. The purpose of this community service activity is to provide an understanding of competitive advantages through the differentiation of shredded fish products with 2 two flavor variants and attractive and hygienic packaging carried out by lecture and discussion methods as well as training in making attractive and hygienic packaging with practical methods. The results showed that there was an increase in understanding of competitive advantages through product and packaging differentiation as well as increased skills in making attractive and hygienic packaging before and after participating in the activity. The conclusion of this activity illustrates that the increase in understanding and skills acquired is beneficial for increasing income and business sustainability